Young people's perspectives on addressing UK health inequalities: utopian visions and preferences for action - Gillian Fergie; Caroline Vaczy; Katherine Smith; Mhairi Mackenzie; Thu Thuy Phan; Shona Hilton (Wiley, 2023)
Abstract Introduction It is increasingly recognised by UK researchers and population health advocates that an important impetus to effective policy action to address health inequalities is activation of public dialogue about the social determinants of health and how inequalities might be addressed. The limited body of existing scholarship reaches varying conclusions on public preferences for responding to health inequalities but with consensus around the importance of tackling poverty. Young people's perspectives remain underexplored despite their increasingly visible role in activism across a range of policy issues and the potential impact of widening inequalities on their generation's health and wellbeing. Methods Six groups of young people (39 in total) from two UK cities (Glasgow and Leeds) were engaged in online workshops to explore views on health inequalities and potential solutions. Inspired by calls to employ notions of utopia, artist-facilitators and researchers supported participants to explore the evidence, debating solutions and imagining a more desirable society, using visual and performance art. Drawing together data from discussions and creative outputs, we analysed participants' perspectives on addressing health inequalities across four domains: governance, environment, society/culture and economy. Findings Proposals ranged from radical, whole‐systems change to support for policies currently being considered by governments across the United Kingdom. The consensus was built around embracing more participatory, collaborative governance; prioritising sustainability and access to greenspace; promoting inclusivity and eliminating discrimination and improving the circumstances of those on the lowest incomes. Levels of acceptable income inequality, and how best to address income inequality were more contested. Individual‐level interventions were rarely presented as viable options for addressing the social inequalities from which health differences emanate. Conclusion Young people contributed wide‐ranging and visionary solutions to debates around addressing the enduring existence of health inequalities in the United Kingdom. Their reflections signal support for 'upstream' systemic change to achieve reductions in social inequalities and the health differences that flow from these. Public Contribution An advisory group of young people informed the development of project plans. Participants shaped the direction of the project in terms of substantive focus and were responsible for the generation of creative project outputs aimed at influencing policymakers.